The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/iub.2127
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavones rich cowpea and vitamin D induces the proliferation and differentiation of human osteoblasts via BMP‐2/Smad pathway activation: Mechanistic approach

Abstract: Isoflavones, such as Genistein (Ge) and Daidzein (Dz) are widely studied Phytoestrogens with potent anti-osteoporotic and good antioxidant activity. Cowpea is one such legume having high isoflavone content and hence we aimed at studying the beneficial effects of the isoflavones isolated from cowpea as it is widely accepted staple food in India. Previously, we reported the effect of Cowpea isoflavones (CP) and Vitamin D (VD) owing to its ability of improving the osteoporotic condition in a diet induced osteopor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…We also briefly summarized the structure and grouping of estrogens and phytoestrogens, especially the bioavailability of isoflavonoids [35,36]. Here, we also showed the effect of phytoestrogens on signal transduction pathways based on recent studies on molecular biology [23,44,45,49,51,58,98].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We also briefly summarized the structure and grouping of estrogens and phytoestrogens, especially the bioavailability of isoflavonoids [35,36]. Here, we also showed the effect of phytoestrogens on signal transduction pathways based on recent studies on molecular biology [23,44,45,49,51,58,98].…”
Section: Discussionmentioning
confidence: 93%
“…The isoflavonoids and vitamin D of cowpea daidzein and genistein together activate the BMP-2/Smad (bone morphogenetic protein-2 growth factor/Smad signal transduction pathways) signaling pathway of osteoblasts in osteogenesis and promote further proliferation and differentiation of osteoblasts. These results showed that isoflavones (daidzein and genistein) isolated from cowpea can be used in the treatment of bone disorders [57,58].…”
Section: Properties Of Phytoestrogens and Their Role In Signal Transd...mentioning
confidence: 92%
See 1 more Smart Citation
“…Several studies have shown that VD has both anabolic and catabolic effects in bone homeostasis by stimulating differentiation, mineralization and bone formation of osteoblasts. [12][13][14] Although the precise effects of VD on osteoblasts may vary with treatment time, dosage, and source of osteoblasts, 15 VD can regulate specific protein expression and signaling pathways related to osteoblast proliferation and differentiation, such as Wnt signaling, 16 bone morphogenetic proteins (BMPs), 17 runt-related transcription factor 2 (Runx2), 14,18 MARK signaling, 19 osteoprotegerin (OPG) and receptor activator of nuclear factor-kappa B ligand (RANKL) signaling pathway. 12,20 Among BMPs, BMP2 is the most effective inducer for osteoblast differentiation and performs a crucial osteogenic function.…”
Section: Introductionmentioning
confidence: 99%